Integrasi Islam dan Sains: Telaah Terhadap Konsep Matematika dalam Hadits Keutamaan Membaca Shalawat - Walidah , Natasya Ziana; Alghar, Muhammad Zia; Abdussakir, Abdussakir; Smeer, Zeid B. (Program Pascasarjana IAIN Langsa, 2024)
National education has the goal of shaping the morals of students who are truehearted and dedicated to God. As part of national education, Islamic-integrated mathematics learning becomes a bridge to achieve this goal. This study aims to explore the concept of mathematics in the hadith with the theme of the virtue of reciting shalawat. This research uses a qualitative approach with literature study methods. Data were obtained from hadith books, hadith applications, articles, and relevant documents. The results showed that there are three mathematical concepts in the hadith related to the virtue of reciting shalawat. The mathematical concepts found include the concept of numbers (natural numbers, integers, positive integers, odd numbers, and even numbers), arithmetic operations (addition operations), and the concept of relations and functions (bijective functions). The results of this study can be used as a reference for learning resources related to Islamic integrated mathematics derived from hadith with the theme of the virtue of reading shalawat.